Biopsychosocial Determinants of Depressive Symptoms among Middle-Aged Adults in Indonesia: Findings from the Indonesian Family Life Survey (IFLS-5) - Sylivia Lugereka; Revi Gama Hatta Novika; Argyo Demartoto; Eti Poncorini Pamungkasari; Setyo Sri Rahardjo (The Indonesian Institute of Science and Technology Research, 2026)
Depression has been recognized as a major public health issue that affects middle-aged people in developing countries. The research explored how diabetes mellitus and stroke history affected depressive symptoms in Indonesian among middle-aged adults. This is a cross-sectional study that used data from the IFLS-5, which included 7,503 participants. Weighted descriptive, bivariate, and multivariable logistic regression analyses were performed. The prevalence of depressive symptoms was 17.72%, while 5.62% reported diabetes and 1.00% reported stroke. In adjusted analysis, diabetes only ((AOR = 0.77; 95% CI: 0.57–1.03; p= 0.082)), stroke only (AOR = 1.32; 95% CI: 0.70–2.52; p= 0.387), and combined diabetes and stroke (AOR = 0.91; 95% CI: 0.18–4.50; p= 0.912) were not significantly associated with depressive symptoms. Female (AOR = 1.20; 95% CI: 1.05–1.39; p= 0.009), unhealthy self-rated health (AOR= 2.48; 95% CI: 2.17–2.84; p= 0.001), and lack of community participation (AOR = 0.86; 95% CI: 0.74–0.99; p= 0.043) were significant. However, BMI had lower odds of depressive symptoms. Marital status, education, residence, smoking status, and physical activity were not significantly associated with depressive symptoms. These findings suggest that psychosocial and perceptual factors play a more prominent role in midlife depressive symptoms than chronic disease status. Integrated public health strategies addressing self-perceived health, social engagement, and gender disparities are necessary.